Clinical Characteristics and Genetic Analysis of a Family With Birt-Hogg-Dubé Syndrome and Congenital Contractural Arachnodactyly - Qiu, Jiayong; Lou, Yao; Zhu, Yingwei; Wang, Min; Peng, Huifang; Hao, Yingying; Jiang, Hongwei; Mao, Yimin (Frontiers in Genetics, 2022)
Background: Birt-Hogg-Dubé (BHD) syndrome and congenital contractural arachnodactyly (CCA) or Beals-Hecht syndrome are clinically rare autosomal dominant genetic diseases. In this study, we describe an extremely rare family with BHD syndrome and CCA. Objective: To investigate the clinical and genetic characteristics of a family with BHD syndrome and CCA. Methods: We describe the clinical characteristics, family history, and clinical manifestations of the patient’s family members. The patient underwent a blood test, computed tomography (CT) of the chest, color Doppler ultrasound of the abdomen and heart, and digital radiography of the hands. Whole exome sequencing was performed on his family members. Results: Two years ago, the male proband developed chest tightness and shortness of breath that was accompanied by an irritating cough as well as repeated (four times) spontaneous pneumothorax. The chest CT indicated spontaneous pneumothorax on the right side and cyst and bullae in both lungs. He had no kidney tumors or skin lesions. His son had a history of pulmonary bullae and experienced spontaneous pneumothorax twice. The proband, his mother, and his son were all born with a hand deformity. The sequencing results demonstrated that both the proband and his son had heterozygous variations of the folliculin (FLCN) gene c.1015C > T (p. Gln339Ter) and fibrillin-2 (FBN2) gene c.3485G > A (p. Cys1162Tyr), which are associated with BHD syndrome and CCA, respectively. Conclusion: For patients with chest tightness, shortness of breath, recurrent spontaneous pneumothorax, and congenital hand deformity without inducement, genetic testing should be carried out as soon as possible to make a clear diagnosis, which can then guide treatment and genetic counseling.